Systematic Literature Review: Analysis Of The Role Of Accounting On Sustainable Tourism Practices, The Influence Of Corporate Social Responsibility And Green Finance Behavior On Indonesia's Tourism - Efrina, Liona; Rahayu, Sri; Yudi, Yudi; Herawaty, Netty (Cita Konsultindo Research Center, 2024)
The tourism industry in Indonesia has grown rapidly in recent years. However, this growth also brings significant environmental and social impacts, such as environmental pollution, exploitation of natural resources, and cultural degradation. Therefore, sustainable tourism is becoming increasingly important to ensure environmental sustainability and the wellbeing of local communities in the long term. Accounting has an important role in supporting sustainable tourism practices. This study aims to determine the role of accounting on sustainable tourism practices, the influence of corporate social responsibility and green finance behavior on Indonesia's tourism sector. This study uses a systematic literature review method. Data is collected through literature searches from academic databases such as Google Scholar. The data collected were analyzed using thematic analysis methods to identify the main themes that emerged from the selected literature. The results of the study show that the role of accounting in sustainable tourism practices is very important because it helps to manage, measure, and report the economic, environmental, and social impacts of tourism activities. In addition, it was found that Corporate Social Responsibility (CSR) and Green Finance behavior towards Indonesia's tourism sector.